Ribociclib Plus Endocrine Therapy in Hormone Receptor-Positive/ERBB2-Negative Early Breast Cancer: 4-Year Outcomes From the NATALEE Randomized Clinical Trial - Fasching, Peter; Stroyakovskiy, Daniil; Yardley, Denise A.; Huang, Chiun Sheng; Crown, John; Bardia, Aditya; Chia, Stephen; Im, Seock Ah; Martin, Miguel; Xu, Binghe; Loi, Sherene; Barrios, Carlos; et al. (JAMA Oncology, 2025)
Importance: Ribociclib plus a nonsteroidal aromatase inhibitor (NSAI) has demonstrated a statistically significant invasive disease-free survival (iDFS) benefit over NSAI alone in patients with hormone receptor-positive/ERBB2 (formerly HER2)-negative early breast cancer. Evaluating the efficacy and safety of adjuvant ribociclib beyond the planned 3-year treatment period is critical for understanding the long-term impact on recurrences. Objective: To evaluate efficacy and safety of adjuvant ribociclib in an exploratory 4-year analysis of the NATALEE (New Adjuvant Trial With Ribociclib [LEE011]) randomized clinical trial, with all patients no longer receiving ribociclib treatment. Design, Setting, and Participants: This exploratory analysis of an international, open-label, randomized phase 3 trial analyzed adjuvant treatment for premenopausal and postmenopausal women and men with hormone receptor-positive/ERBB2-negative early breast cancer. Eligible patients had anatomic stage IIA (either N0 with additional risk factors or N1 [1-3 axillary lymph nodes]), IIB, or III disease per the American Joint Committee on Cancer Staging Manual, eighth edition. The data cutoff date was April 29, 2024. Interventions: Patients were randomized 1:1 to receive ribociclib (400 mg once daily, days 1-21 of a 28-day cycle, over 36 months) plus NSAI (letrozole, 2.5 mg, or anastrozole, 1 mg, once daily continuously for 60 months) or NSAI alone. Men and premenopausal women also received goserelin (3.6 mg once every 28 days administered subcutaneously). Main Outcomes and Measures: The primary end point was iDFS, and secondary efficacy end points included distant disease-free survival, recurrence-free survival, and overall survival. Survival was evaluated by the Kaplan-Meier method. Results: Among 5101 patients included in the analysis (median [range] age, 52 [24-90] years; 5081 [99.6%] female), the median follow-up for iDFS was 44.2 months (range, 0-63 months). Ribociclib plus NSAI continued to show iDFS benefit over NSAI alone (hazard ratio, 0.72; 95% CI, 0.61-0.84), with 3-year iDFS rates of 90.8% vs 88.1% (difference, 2.7 percentage points) and 4-year rates of 88.5% vs 83.6% (difference, 4.9 percentage points). The efficacy benefit was consistent across subgroups and secondary end points. Overall survival data remain immature, although a trend in favor of ribociclib plus NSAI over NSAI alone was observed (hazard ratio, 0.83; 95% CI, 0.64-1.07). The incidence of adverse events has remained stable. Conclusions and Relevance: This exploratory analysis of the NATALEE randomized clinical trial, with a median follow-up beyond the 3-year treatment duration, demonstrated consistent iDFS benefit with ribociclib plus NSAI over NSAI alone. Trial Registration: ClinicalTrials.gov Identifier: NCT03701334.
CRIS-Team Scopus Importer:2025-11-28